2022
DOI: 10.3390/ma15175810
|View full text |Cite
|
Sign up to set email alerts
|

Gd/Mn Co-Doped CaBi4Ti4O15 Aurivillius-Phase Ceramics: Structures, Electrical Conduction and Dielectric Relaxation Behaviors

Abstract: In this work, Gd/Mn co-doped CaBi4Ti4O15 Aurivillius-type ceramics with the formula of Ca1-xGdxBi4Ti4O15 + xGd/0.2wt%MnCO3 (abbreviated as CBT-xGd/0.2Mn) were prepared by the conventional solid-state reaction route. Firstly, the prepared ceramics were identified as the single CaBi4Ti4O15 phase with orthorhombic symmetry and the change in lattice parameters detected from the Rietveld XRD refinement demonstrated that Gd3+ was successfully substituted for Ca2+ at the A-site. SEM observations further revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
2
0
2
Order By: Relevance
“…Senyawa Aurivillius CaBi 4 Ti 4 O 15 yang didoping Gd/Mn dengan formula Ca 1-x Gd x Bi 4 Ti 4 O 15 /0,2Mn berfasa tunggal berhasil disintesis. Analisis lanjutan dengan refinement Rietveld menunjukkan bahwa Gd 3+ berhasil menggantikan Ca 2+ di situs A. Peningkatan nilai x menunjuk-kan perilaku relaksor feroelektrik pada material [7]. Peningkatan komposisi dopan pada senyawa Aurivillius lapis empat Ca 1-x Bi 3+x LaTi 4-x Mn x O 15 meningkatkan nilai konstanta dielektrik yang dihasilkan akibat distorsi struktur [8].…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Senyawa Aurivillius CaBi 4 Ti 4 O 15 yang didoping Gd/Mn dengan formula Ca 1-x Gd x Bi 4 Ti 4 O 15 /0,2Mn berfasa tunggal berhasil disintesis. Analisis lanjutan dengan refinement Rietveld menunjukkan bahwa Gd 3+ berhasil menggantikan Ca 2+ di situs A. Peningkatan nilai x menunjuk-kan perilaku relaksor feroelektrik pada material [7]. Peningkatan komposisi dopan pada senyawa Aurivillius lapis empat Ca 1-x Bi 3+x LaTi 4-x Mn x O 15 meningkatkan nilai konstanta dielektrik yang dihasilkan akibat distorsi struktur [8].…”
Section: Pendahuluanunclassified
“…Besarnya ukuran kristal dari senyawa Aurivillius Ca 1-x Ba x Bi 3,5 La 0,5 Ti 4 O 15 ditampilkan pada Tabel 1. Ukuran kristal terlihat menurun dengan kenaikan nilai x. Penurunan ukuran kristal disebabkan oleh beberapa faktor, seperti laju difusi antara ion Ba 2+ dan Ca 2+ mempengaruhi laju pertumbuhan kristal di berbagai arah, yang berkontribusi pada pembentukan kristal dengan ukuran yang lebih kecil [7]. Selain itu, penambahan ion Ba 2+ dengan jari-jari ion yang lebih besar terhadap ion Ca 2+ menghasilkan tegangan dalam kisi kristal, yang menyebabkan pembentukan lebih banyak cacat atau dislokasi dan membatasi pertumbuhan kristal [13].…”
Section: Hasil Dan Diskusi 31 Hasil Analisis Pola Difraksi Sinar-x Id...unclassified
“…There exist several research reports where scientists have reported their work on improving the values of remnant polarization ( P r ), d 33 and T C by modifying fabrication techniques or by doping the ions at A and B sites of CBT. Recently, Wu et al reported the fabrication of Gd/Mn co-coped CaBi 4 Ti 4 O 15 ceramics, where a high dc conduction activation energy value of 1.87 eV was reported [ 18 ]. Xi et al fabricated a Ca 0.85 (LiCe) 0.075 Bi 4 Ti 4− x Zn x O 15 ceramic system and reported a high d 33 of 20 pC/N [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of [20] reported the effects of oxide additives on the phase structures and electrical properties of SrBi 4 Ti 4 O 15 high-temperature piezoelectric ceramics. The authors of [21] revealed the structures, electrical conduction and dielectric relaxation behaviors of the Gd/Mn co-doped CaBi 4 Ti 4 O 15 Aurivillius-phase ceramics. By means of the chemical (substituting ions and oxide additives) modification and microstructural (phase composition and grain size/orientation) design for these three kinds of BLSFs ceramics, the electrical properties of materials were greatly improved.…”
mentioning
confidence: 99%